Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco - Volcan, Matheus Vieira; Severo-Neto, Francisco (Zootaxa, 2019)
A new species of Austrolebias belonging to the A. bellottii species group is herein described from the Brazilian Chaco, Mato Grosso do Sul state, constituting the northernmost record of the genus in Brazil, as well as the first record of this genus on the left bank of the Rio Paraguai. The new species is distinguished from all other species of the A. bellottii group by the following combination of characters: pectoral fin posterior margin reaching vertical between base of 4th and 7th anal fin rays in females, a high number of gill rakers in the first branchial arch, a lower head width in both sexes, and a small number of neuromasts in the preopercular series. Additionally, we provide information on ecology and the conservation status of the new species.